Immigrants' Returns Intentions and Job Search Behavior When the Home Country Is Unsafe - Jacopo Bassetto; Teresa Freitas Monteiro (Center for Economic Studies and ifo Institute (CESifo), 2024)
Migration is often temporary, and the intended length of stay in the host country is an important determinant of immigrants' labor market behavior, human capital investment, and socioeconomic integration. In this paper, we investigate whether safety conditions in the home country affect immigrants' return intentions and job search behavior. We combine administrative and survey data with precise information on terrorist attacks worldwide. Our identification strategy exploits the quasi-random occurrence of terrorist attacks in the home country relative to the timing of interviews and job separations in Germany. We show that immigrants interviewed after a terrorist attack in their home country are 12 percentage points more likely to wish to remain in Germany permanently. Immigrants react more strongly if they are less integrated in Germany and have close family members in their home country. Consistent with the prediction that revisions to the intended length of stay affect immigrants' labor market behavior, we show that immigrants who enter unemployment when a terrorist event hits their home country are 1.8 percentage points more likely to be employed within three months than immigrants who enter unemployment in quiet times. Among those who find employment within three months, immigrants who experience terror events receive lower hourly wages and are more likely to work part-time. These results suggest that immigrants who enter unemployment in a month with high levels of violence in the home country trade immediate job security for lower earnings and less-productive firms.
Keywords: J15; J61; J64; 330; immigration; uncertainty; violence; return migration; unemployment